2017
DOI: 10.1021/acs.macromol.6b02041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicone Elastomers Containing Silyl-Based Polymer-Grafted Carbonyl Iron Particles: An Efficient Way To Improve Magnetorheological, Damping, and Sensing Performances

Abstract: The synthesis and characterization of isotropic magnetorheological elastomer (MRE) with significantly enhanced utility properties is presented. Common drawbacks of classical MREs, such as poor particle wettability, dispersibility, low thermooxidative stability, low chemical stability, and insufficient durability, were eliminated by grafting the carbonyl iron (CI) particles with poly(trimethylsilyloxyethyl methacrylate) (PHEMATMS) using surface-initiated atom transfer radical polymerization (ATRP). Two sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 45 publications
10
96
0
Order By: Relevance
“…Due to these facts the heat redistribution in the sample is more complicated and transformation from light to mechanical energy needs more time. As was also investigated by our group, the short polymer chains act as plasticizers, and even if they are grafted from the reinforcing surface like carbon nanotubes or carbonyl iron, the mechanical properties are lower [10,15,51]. In good agreement with the literature, all types of polymer chains grafted from GO provided a plasticizing effect, therefore the photo-actuation performance was better in comparison to the neat GO.…”
Section: Discussionsupporting
confidence: 84%
“…Due to these facts the heat redistribution in the sample is more complicated and transformation from light to mechanical energy needs more time. As was also investigated by our group, the short polymer chains act as plasticizers, and even if they are grafted from the reinforcing surface like carbon nanotubes or carbonyl iron, the mechanical properties are lower [10,15,51]. In good agreement with the literature, all types of polymer chains grafted from GO provided a plasticizing effect, therefore the photo-actuation performance was better in comparison to the neat GO.…”
Section: Discussionsupporting
confidence: 84%
“…Martin et al [ 62 ] reported the characteristics of MREs by coating poly(trimethylsilyloxyethyl methacrylate) (PHEMATMS) on the surface of CI particles, in which the CI-g-PHEMATMS particles showed about 6.2% reduction in magnetization than neat CI particles due to the 10–20 nm coating thickness. However, it was possible to improve thermo-oxidation stability and anti-acid/corrosion properties through polymer coating.…”
Section: Mre Materialsmentioning
confidence: 99%
“…Since, the intended application of the prepared fiber mats is the photo-actuation, which is the dynamic process of reversible actuation upon certain force and frequency, the DMA investigations have been performed. Moreover, the position of the glass transition can also provide additional information about polymer chain mobility as we published previously [5]. Storage modulus represents reversible energy given by material upon dynamic mechanical stimulation, which is an important factor for elucidation of the mechanical performance.…”
Section: Characterization Of the Non-woven Fiber Matsmentioning
confidence: 92%
“…Smart systems belong to the group of materials capable of changing the basic properties, when they are exposed to external stimuli such as electric [1][2][3], magnetic [4,5], thermal [6,7], pH [8,9], or light [10,11]. In case of light stimulation, such smart systems can exhibit the shape [12] or resistivity [13] change or generate electric output [14].…”
Section: Introductionmentioning
confidence: 99%